Analysis of Treatment Goals for Patients with Schizophrenia: A US Survey of Psychiatrists, Patients with SCZ and Caregivers. (April 2021) - Chen, Maxine; Shepherd, Jason; Bailey, Hollie; Wright, Jack; Fitzgerald, Heather M.
Abstract: Objectives: Objectives for this survey are to determine similarities or differences in treatment goals reported by psychiatrists, patients with schizophrenia (SCZ) and caregivers in the US, as well as whether goals differed by patients currently on an oral antipsychotic (OAP) or long-acting injectable (LAI), and whether goals differed by age. Methods: This was a real-world, cross-sectional survey of US psychiatrists, patients =18 years old diagnosed with SCZ, and caregivers. Data was collected using the Disease Specific Programme (DSP) methodology. Psychiatrists (n=120) completed detailed record forms for next 8 outpatients and 2 inpatients matching inclusion criteria. The same patients and their caregivers, if present, were invited by their psychiatrist to voluntarily complete a separate survey. Results: Responses on treatment goals were collected from psychiatrists for all patients included in the analysis (n=1161), patients (n= 542) and caregivers (n=130). Among 3 top goals, psychiatrists, patients and caregivers concurred that "decrease in disease symptoms" is most important (63%, 64%, 68% respectively). For psychiatrists and caregivers, second was "decrease in hospitalization for relapse" (41%, and 38% respectively), whereas for patients, it was "thinking clearly" (47%). Of the 3 least important goals, psychiatrists, patients and caregivers agreed with "sexual problems" (59%, 43%, 44%, respectively) and "weight gain" (38%, 44%, 38%, respectively). When asked which goals were met by current medication, patients responded "decrease in disease symptoms" (68%) and "thinking clearly" (39%). However, caregivers responded "thinking clearly" (30%) was not met by current medication. Caregivers most important goals, "decrease in disease symptom" (70%) and "decrease in hospitalization for relapse" (41%), were met. Additional analyses of patients on OAPs and LAIs, did not show differences in goals. However, "decrease in disease symptoms" was numerically more important for patients on LAIs vs OAPs according to psychiatrists (68% vs 62%) and caregivers (77% vs 70% respectively). Caregivers responded "decrease in hospitalization for relapse" was met for 63% patients currently on an LAI and 35% OAP. No major differences in treatment goals were observed by patient age (18–35 vs 36–65 vs >65 years). Discussion: There is consensus among US psychiatrists, patients and caregivers on the most important treatment goal "decrease in disease symptoms", regardless of patients' current medication or age. For patients, "thinking more clearly" was second, compared with "decrease in hospitalization due to relapse", for psychiatrists and caregivers. All agreed that least important treatment goals, related to AEs, were "weight gain" and "sexual problems". More caregivers agreed "decrease in hospitalization for relapse" was met by patients on LAIs vs OAPs. These findings may help with discussions between psychiatrists, patients and caregivers. Funding: Lundbeck LLC and Otsuka Pharmaceutical Development & Commercialization, Inc.